On the Gottlieb groups Gn+k(M(Zm ‘Z2, n)) for k = 1, 2 - Golasiński, Marek; Melo, Thiago de [UNESP]; Bononi, Rodrigo [UNESP] (Odesa National University of Technology, 2024)
We are motivated by [M. Arkowitz. K. Maruyama. J. Math. Soc. Japan, 66(3):735–743, 2014]: “It would be interesting to compute other Gottlieb groups of Moore spaces such as, for example, Gn+1(M(A, n))” to compute the Gottlieb groups Gn+k(M(Zm ‘Z2, n)) for k = 1, 2 and m ě 1.
Keywords: Euler-Poincaré number; finitely generated Abelian group; Gottlieb group; Moore space; smash (wedge) product; suspension; Whitehead product